Older LGBT Adults’ End-of-Life Conversations: Findings from Nova Scotia, Canada - Gahagan, Jacqueline; Humble, Áine M.; Gutman, Gloria M.; de Vries, Brian (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
Although increasing research attention in North America is being paid to the health and social disparities experienced among older lesbian, gay, bisexual, and transgender (LGBT) populations, end-of-life (EOL) preparations among these populations are not yet well understood. This study explored older LGBT individuals’ EOL preparations and service providers’ perceptions of such provisions. In this qualitative study, we conducted three focus groups with 15 LGBT adults aged 60 and older who have at least one chronic health condition and live in Nova Scotia. We also conducted one focus group with four service providers. We identified four themes: (a) LGBT communities of care have changed over time, (b) difficulties in asking others for help, (c) hesitancy in thinking about end-of-life, and (d) varying views on the helpfulness of internet technology. The findings illustrate ongoing tensions between being “out” about one’s sexual orientation or gender identity and being able to engage with social and health care providers in determining EOL planning.